Telemental Health Approaches for Rural Opioid Use Treatment: An Integrative Review - Jayme K. Weber; Roxanne K. Vandermause; Cynthia M. Schmidt (Journal of the American Psychiatric Nurses Association, 2026)
Background: Opioid use disorder (OUD) continues to disproportionately impact rural communities. Telemental health (TMH) offers a promising strategy to bridge this divide, especially in the context of expanding telehealth-delivered medication for OUD (tele-MOUD). Aim: The purpose of this review was to examine the current evidence on TMH approaches for treating OUD among rural adults. Methods: Databases including EMBASE, MEDLINE, CINAHL, PsycINFO, Scopus, the Cochrane Library, and ClinicalTrials.gov were searched in July 2024. Searches were updated in May and November 2025. All studies of TMH care for OUD in rural, adult populations were included. After eligibility screening, findings were synthesized from 23 empirical studies published between January 2022 and November 2025. Reviews published during the pandemic highlighted the need for research in this area. The quality of the evidence was assessed with the Mixed Methods Appraisal Tool (MMAT). Results: In rural settings, TMH demonstrated greater access, retention, and patient satisfaction than traditional in-person care. Tele-mentoring expanded treatment capacity and supported provider confidence. However, disparities in broadband access, digital literacy, stigma, and organizational readiness hinder equitable implementation. Younger clients experienced lower retention, and low-income clients experienced limited access to video-based care. TMH was found to reduce public stigma, but stigma reduction education, particularly for frontline staff and pharmacies, is needed. Conclusions: Telemental health offers a scalable solution to rural OUD treatment inequities, but its success hinges on policy support, digital infrastructure investment, and culturallyresponsive, community-engaged implementation strategies. Future research should address long-term outcomes, standardized metrics, and broader innovations beyond tele-MOUD.